PERJANJIAN YANG DI LARANG DALAM USAHA TIDAK SEHAT TERHADAP PERBEDAAN HARGA TANGGA DI TOKO BANGUNAN PEKANBARU - Hafis Ryadhie; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Business competition is competition between competition in carrying out production and marketing activities of goods and services. Competition is a strategy to advance the company by producing good quality products through new discoveries and ways to run a better company. This kind of competition is fair competition, where competition is justified by law and brings profits without harming competition. In addition to fair business competition there is unfair business competition, which is business competition that is carried out not in competition, against the law, and against competition.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at the CA Building Store, while the population and sample were CA Store Owners, Building Stores that sell the same items and Consumers. Data sources used are primary data and secondary data. Data collection techniques in this study were interviews, questionnaires, and literature review.The conclusions that can be obtained from the results of the study are First, the Practice of the Prohibited Agreement in Unfair Business Competition Against the Difference in Price of Stairs in Pekanbaru Building Stores has often happened one of them as did the CA shop. Prohibited agreements are included in the Pricing category, whereby the business actors agree to jointly determine the price of goods / services on the market for the benefit of the business actor. Article 5 Paragraph (1). Second, Efforts to Overcome the Practices of Prohibited Agreements in Unfair Business Competition Against Stairs Price Differences in Pekanbaru Building Stores, namely by reporting to the Business Competition Supervisory Commission (KPPU).Keywords: Business Competition, Prohibited Agreements, Building Stores, Stair Prices, Pricing.